When credit expansions become troublesome: The story of investor sentiments - Eddie Gerba; Danilo Leiva Leon; Johannes Pöschl (Danmarks Nationalbank, 2023)
Identifying the drivers of credit cycles is crucial for prudential regulation. We show in a model that investor sentiments result in excessive asset price movements, leading to sharp credit reversals. Motivated by this, we decompose fluctuations in stock prices into fundamental and noise shocks and estimate their effects on credit. Both shocks lead to a credit expansion, but only a noise shock results in a reversal if the anticipated shock fails to realise. Noise shocks have stronger effects when risk premiums are low. A novel debt overhang channel is important for the propagation of noise shocks.
Keywords: E44; G24; G28; 330; Credit cycles; news shocks; noise shocks; debt overhang; bank lending